Keterampilan Dasar Mengajar Guru PAI pada Kurikulum Merdeka: Implementasi Proyek Penguatan Profil Pelajar Pancasila di SD Negeri 02 Curup - Apriliya, Rosety (Belajea: Jurnal Pendidikan Islam, 2024)
The position of the teacher has a very important meaning in education, namely the duties and responsibilities of teachers which are quite heavy to educate their students. Thus, it requires a teacher to equip himself with various skills which are expected to help him carry out his duties and achieve the goals of education itself and it is hoped that the teacher can optimize his role in the classroom. This research is field research, in this case the researcher uses a descriptive approach, namely only collecting facts and explaining them thoroughly and researching according to the problem to be solved. And using qualitative analysis, namely analyzing and presenting facts by ordering words or detailing them so that they are easier to understand. Based on the analysis above by matching research results with theory, it is clear to conclude that PAI teachers at SD Negeri 02 Curup are skilled in teaching. If we look at the three aspects of teaching skills, it can produce quality and achieving students.